1960
DOI: 10.1161/01.cir.22.3.419
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Indirect and Direct Arterial Pressures

Abstract: Bilateral determinations of the blood pressures were made nonsimultaneously and simultaneously by the indirect method under basal conditions on 447 patients. In this group 26.6 per cent of the paired measurements by the nonsimultaneous indirect method exhibited systolic differences of 10 mm. Hg or greater and 15 per cent exhibited diastolic differences of this magnitude, whereas only 5.3 per cent of the measurements by the simultaneous indirect method had systolic differences and only 4 per cent had diastolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
52
1

Year Published

1967
1967
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 22 publications
13
52
1
Order By: Relevance
“…Although our prevalence figures of 23% with a sIAD X10 mm Hg and 6% with a dIAD X10 mm Hg are lower than the figures that we and others have reported previously from primary care, 3,7,15,16 they are close to the best estimates we have calculated from the most methodologically robust studies. 4 We had anticipated a higher prevalence of the IAD than we reported previously, as it has been shown to occur more frequently in hypertensive than normotensive populations in selective studies, 4,[17][18][19] but no previous series of hypertensive patients reported from primary care was available to support this contention. The final prevalence figures were lower than those in our interim report 3 on this cohort, but we have previously shown that prevalence will fall with repeated pairs of measurements.…”
Section: Discussionmentioning
confidence: 93%
“…Although our prevalence figures of 23% with a sIAD X10 mm Hg and 6% with a dIAD X10 mm Hg are lower than the figures that we and others have reported previously from primary care, 3,7,15,16 they are close to the best estimates we have calculated from the most methodologically robust studies. 4 We had anticipated a higher prevalence of the IAD than we reported previously, as it has been shown to occur more frequently in hypertensive than normotensive populations in selective studies, 4,[17][18][19] but no previous series of hypertensive patients reported from primary care was available to support this contention. The final prevalence figures were lower than those in our interim report 3 on this cohort, but we have previously shown that prevalence will fall with repeated pairs of measurements.…”
Section: Discussionmentioning
confidence: 93%
“…Of the 447 patients studied by Harrison et al (1960) with nonsimultaneous measurements, 27 % had systolic differences and 15 % had diastolic differences in excess of 10 mmHg for individual recordings. When the indirect readings were made simultaneously the respective percentages were 5 % for systolic and 4 % for diastolic pressures.…”
Section: Resultsmentioning
confidence: 98%
“…It is not suprising, therefore, to find wide interarm differences in single indirect readings, although these are greatly diminished by taking the average of several readings. Even if great care is taken to ensure that exactly the same technique is followed for each measurement, that comparative measurements are made simultaneously with cuffs of the same dimensions, and that the instruments used are accurate and give the same readings when checked against each other, variable differences will be found (Allen and Hines 1939;Harrison et al, 1960). …”
Section: Resultsmentioning
confidence: 99%
“…[36][37][38][39][40][41] Studies looking specifically at left or right handedness have also failed to demonstrate an association with the higher-reading arm. 33,42 In the current study, blood pressures were recorded in a fixed sequence for anklebrachial index assessment, 18 which may account for the bias towards higher rightarm blood pressures observed through order effects.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%